Polymeric Amorphous Solid Dispersions of Dasatinib: Formulation and Ecotoxicological Assessment - Katarina Sokač; Martina Miloloža; Dajana Kučić Grgić; Krunoslav Žižek (MDPI AG, 2024)
Dasatinib (DAS), a potent anticancer drug, has been subjected to formulation enhancements due to challenges such as significant first-pass metabolism, poor absorption, and limited oral bioavailability. To improve its release profile, DAS was embedded in a matrix of the hydrophilic polymer polyvinylpyrrolidone (PVP). Drug amorphization was induced in a planetary ball mill by solvent-free co-grinding, facilitating mechanochemical activation. This process resulted in the formation of amorphous solid dispersions (ASDs). The ASD capsules exhibited a notable enhancement in the release rate of DAS compared to capsules containing the initial drug. Given that anticancer drugs often undergo limited metabolism in the body with unchanged excretion, the ecotoxicological effect of the native form of DAS was investigated as well, considering its potential accumulation in the environment. The highest ecotoxicological effect was observed on the bacteria Vibrio fischeri, while other test organisms (bacteria Pseudomonas putida, microalgae Chlorella sp., and duckweed Lemna minor) exhibited negligible effects. The enhanced drug release not only contributes to improved oral absorption but also has the potential to reduce the proportion of DAS that enters the environment through human excretion. This comprehensive approach highlights the significance of integrating advances in drug development while considering its environmental implications.